Matkowski-Type Functional Contractions under Locally Transitive Binary Relations and Applications to Singular Fractional Differential Equations - Faizan Ahmad Khan; Nidal H. E. Eljaneid; Ahmed Alamer; Esmail Alshaban; Fahad Maqbul Alamrani; Adel Alatawi (Fractal and Fractional, 2024)
This article presents a few fixed-point results under Matkowski-type functional contractive mapping using locally <semantics>J</semantics>-transitive binary relations. Our results strengthen, enhance, and consolidate numerous existent fixed-point results. To argue for the efficacy of our results, several illustrated examples are supplied. With the help of our findings, we deal with the existence and uniqueness theorems pertaining to the solution of a variety of singular fractional differential equations.